Religion and Mental Well-being: A Phenomenological Research on Individual Experiences in Interaction with the Qur'an among Pepadun Muslims in Lampung - Abrori, M. Sayyidul (Bulletin of Counseling and Psychotherapy, 2023)
This research raises the topic of the relationship between religion, mental well-being, and local cultural wisdom in pepadun Muslim communities in the interior of Lampung. It was found that the understanding and practice of religion in this community positively impacted mental well-being, became an inner bond that provided physical and spiritual calm, and strengthened the spiritual relationship with God through interaction with the Koran. Researchers found differences between the religious practices of pepadun Muslims and urban Muslims, especially in socio-religious practices. The higher level of solidarity among pepadun Muslims indicates that they live communally and socially. Assimilation of local wisdom, such as Nemui Nyimah and Piil Pesenggiri, becomes a critical element of these communities' religious understanding and practice, becoming the cultural foundation that gives uniqueness to their religious life. This research provides insight into the dynamics of the relationship between religion, mental well-being, and local cultural wisdom but also confirms that religious and cultural values ​​play an essential role in shaping the religious insight and mental well-being of the Pepadun Muslim community in the interior of Lampung.